2007
DOI: 10.1002/bit.21598
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simple and rapid method for producing non‐fucosylated oligomannose containing antibodies with increased effector function

Abstract: Glycosylation in the Fc region of antibodies has been shown to play an important role in antibody function. In the current study, glycosylation of human monoclonal antibodies was metabolically modulated using a potent alpha-mannosidase I inhibitor, kifunensine, resulting in the production of antibodies with oligomannose-type N-glycans. Growing Chinese hamster ovary cells for 11 days in batch culture with a single treatment of kifunensine was sufficient to elicit this effect without any significant impact on ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
174
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(183 citation statements)
references
References 53 publications
7
174
2
Order By: Relevance
“…Both cell lines deleted for the fucosyl transferase gene and cell lines treated with fucosyl transferase inhibitors express IgG1 afucosylated or poorly fucosylated (Zhou et al. 2008; Ferrara et al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Both cell lines deleted for the fucosyl transferase gene and cell lines treated with fucosyl transferase inhibitors express IgG1 afucosylated or poorly fucosylated (Zhou et al. 2008; Ferrara et al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, IgG antibody expressing hybridoma cells generated exclusively oligomannose structures (Man9 to Man5) if the cells were exposed to 80-100 ng/mL kifunensine throughout the culture. At intermediate kifunensine concentrations (40-60 ng/mL), oligomannose abundance settled in the range of 69 to 90% and decreased to about 18% at 20 ng/mL of kifunensine 91 . It is not surprising that they concluded that kifunensine is effective in producing antibodies with oligomannose-type glycans from CHO cells, as no impact on both titer and viability but only on maximum viable cell density was observed.…”
Section: High Mannose Speciesmentioning
confidence: 96%
“…As a result, selective inhibition of sialic acid addition by adding a fluorinated sialic acid analog increases fucosylation 112 . Due to its effective inhibition of steps occurring prior to fucose attachment, kifunensine effectively retains oligomannose residues and hence allows to express non fucosylated proteins at concentrations beyond 60 ng/mL 91 . It is important to take into account the existence of a mannosyl-glycoprotein-N-acetylglucosaminyltransferase I-independent (GnT I) fucosylation pathway, as described by various authors when modulating the glycosylation levels, since inhibition of GnT does not necessarily prevent further processing of the oligosaccharide chain including fucosylation.…”
Section: Fucosylationmentioning
confidence: 99%
See 2 more Smart Citations